2019
DOI: 10.3390/toxins11020109
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Aspergillus and Fusarium Mycotoxins in Africa: Benefits and Limitations

Abstract: Fungal contamination and the consequent mycotoxin production is a hindrance to food and feed safety, international trade and human and animal health. In Africa, fungal contamination by Fusarium and Aspergillus is heightened by tropical climatic conditions that create a suitable environment for pre- and postharvest mycotoxin production. The biocontrol of Fusarium and its associated fusariotoxins has stagnated at laboratory and experimental levels with species of Trichoderma, Bacillus and atoxigenic Fusarium bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 49 publications
(69 reference statements)
1
60
0
1
Order By: Relevance
“…Whereas some researchers have critical opinion regarding biocontrol of aflatoxins [116][117][118][119][120], substantial research conducted with field and tree crops has shown that using atoxigenic isolates of A. flavus as biocontrol agents is one of the most effective pre-harvest management strategies for reducing aflatoxin contamination (Figure 3). The extensive research demonstrating the efficacy, safety, and benefits of the technology have allowed registration of several aflatoxin biocontrol products with regulatory authorities.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas some researchers have critical opinion regarding biocontrol of aflatoxins [116][117][118][119][120], substantial research conducted with field and tree crops has shown that using atoxigenic isolates of A. flavus as biocontrol agents is one of the most effective pre-harvest management strategies for reducing aflatoxin contamination (Figure 3). The extensive research demonstrating the efficacy, safety, and benefits of the technology have allowed registration of several aflatoxin biocontrol products with regulatory authorities.…”
Section: Discussionmentioning
confidence: 99%
“…These favourable environmental conditions are enhanced by the vulnerability of the prevailing agricultural systems. Farming activities are essentially managed for subsistence by smallholders facing technical and socio-economic challenges that hamper any efforts to restrain aflatoxin contamination [71][72][73]. Moreover, the staple crops grown, such as peanut, maize, sorghum, rice, sunflower, and cottonseed are good substrates for aflatoxin production [74][75].…”
Section: Crop Contaminationmentioning
confidence: 99%
“…The main obstacles for biocontrol agents are due to the lack of consistency when microbial inoculants are applied under complex environmental conditions, and to the complexity of finding appropriate formulation and timing for application [48]. Biological, ecological, toxicological, and regulatory cost factors also influence the effectiveness and marketability of biological control products [49].…”
Section: Critical Assessment Of Literaturementioning
confidence: 99%